2013
DOI: 10.1212/wnl.0b013e31829bfd63
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance frequency shifts during acute MS lesion formation

Abstract: These findings suggest that an increase in MR frequency does not simply reflect blood-brain barrier disruption or edema; rather, it reflects a change of tissue architecture as a consequence of new lesion formation. The data demonstrate that the MR frequency of focal MS lesions is increased before the lesions appear on conventional MRI. Unlike many other advanced imaging techniques, the images for frequency mapping can be rapidly acquired at high spatial resolution and standardized on most clinical scanners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 41 publications
(37 reference statements)
4
73
2
2
Order By: Relevance
“…Following the acute stage, a significant increase in both QSM and R2 * occurs in lesions that are no longer enhancing, yet under one year of age, suggesting that iron release occurs during the early stages after myelin destruction. 21 These findings are consistent with the release of iron secondary to myelin and oligodendrocyte destruction 9, 35 and provides a source for iron-laden proinflammatory M1 microglia and for iron-driven amplification of oxidative stress within the acute MS lesion. 2, 36 Studies have shown evidence for oxidative stress damage to oligodendrocytes, mitochondrial and dystrophic axons in acute MS lesions, 37 which consequently inhibit endogenous remyelination.…”
Section: Discussionsupporting
confidence: 60%
“…Following the acute stage, a significant increase in both QSM and R2 * occurs in lesions that are no longer enhancing, yet under one year of age, suggesting that iron release occurs during the early stages after myelin destruction. 21 These findings are consistent with the release of iron secondary to myelin and oligodendrocyte destruction 9, 35 and provides a source for iron-laden proinflammatory M1 microglia and for iron-driven amplification of oxidative stress within the acute MS lesion. 2, 36 Studies have shown evidence for oxidative stress damage to oligodendrocytes, mitochondrial and dystrophic axons in acute MS lesions, 37 which consequently inhibit endogenous remyelination.…”
Section: Discussionsupporting
confidence: 60%
“…By omitting the acquisition of the sagittal 2D-FLAIR, the 2D proton density-weighted image, and potentially the DIR, approximately 20 minutes of acquisition time is saved, which can be invested in acquiring 3D sequences at higher spatial resolution, for instance. In research studies, the remaining scanning time can also be used in the acquisition of advanced MR images, such as myelin water, 26 magnetization transfer imaging, 27 or susceptibility-weighted imaging [28][29][30] for the calculation of frequency maps as measures of MS tissue damage 31 and of R2* maps.…”
Section: Considerations For Data Acquisitionmentioning
confidence: 99%
“…Previous studies have reported changes in acute MS lesions regarding MR imaging frequency shift, 10 magnetization transfer ratio, 11 and relaxation values, 12 suggesting the possibility of using quantitative methods to distinguish and characterize the acute lesions. However, so far no method has met the requirements necessary to be considered fully clinically applicable.…”
mentioning
confidence: 99%